Escherichia coli avoids high dissolved oxygen stress by activation of SoxRS and manganese-superoxide dismutase - Baez, Antonino (BioMed Central, 2013)
BACKGROUND: High concentrations of reactive oxygen species (ROS) were reported to cause oxidative stress to E. coli cells associated with reduced or inhibited growth. The high ROS concentrations described in these reports were generated by exposing the bacteria to H(2)O(2) and superoxide-generating chemicals which are non-physiological growth conditions. However, the effect of molecular oxygen on oxidative stress response has not been evaluated. Since the use of oxygen-enriched air is a common strategy to support high density growth of E. coli, it was important to investigate the effect of high dissolved oxygen concentrations on the physiology and growth of E. coli and the way it responds to oxidative stress. RESULTS: To determine the effect of elevated oxygen concentrations on the growth characteristics, specific gene expression and enzyme activity in E. coli, the parental and SOD-deficient strain were evaluated when the dissolved oxygen (dO(2)) level was increased from 30% to 300%. No significant differences in the growth parameters were observed in the parental strain except for a temporary decrease of the respiration and acetate accumulation profile. By performing transcriptional analysis, it was determined that the parental strain responded to the oxidative stress by activating the SoxRS regulon. However, following the dO(2) switch, the SOD-deficient strain activated both the SoxRS and OxyR regulons but it was unable to resume its initial growth rate. CONCLUSION: The transcriptional analysis and enzyme activity results indicated that when E. coli is exposed to dO(2) shift, the superoxide stress regulator SoxRS is activated and causes the stimulation of the superoxide dismutase system. This enables the E. coli to protect itself from the poisoning effects of oxygen. The OxyR protecting system was not activated, indicating that H(2)O(2) did not increase to stressing levels.